Peran Kebijakan Fiskal Dalam Mengevaluasi Zakat Sebagai Upaya Menyikapi Kemiskinan Di Indonesia - Hamdiah, Vidairotul (Jurnal Ilmiah Ekonomi Islam, 2024)
This research aims to evaluate the role of zakat in reducing poverty levels in Indonesia with a focus on fiscal policy. Islam teaches that poverty stems from unequal access to basic needs, and zakat is considered a potential instrument in overcoming social and economic inequality. Even though the government has made efforts to overcome poverty, the poverty rate in Indonesia is still high. This research uses qualitative methods with a library research approach to analyze literature related to fiscal policy, zakat, and Islamic economic concepts. The research results show that zakat has a positive impact in reducing poverty, especially through providing business capital. However, implementing zakat in Indonesia requires an evaluation of fiscal policy, and low public trust in zakat institutions is an obstacle. Therefore, the role of supportive, transparent and efficient fiscal policies in zakat management is very important to increase the impact of zakat in alleviating poverty.